2011
DOI: 10.1016/j.biomaterials.2010.08.101
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell homing in musculoskeletal injury

Abstract: The regenerative potential of injured adult tissue suggests the physiological existence of cells capable of participating in the reparative process. Recent studies indicate that stem-like cells residing in tissues contribute to tissue repair and are replenished by precursor bone marrowderived cells. Mesenchymal stromal cells (MSC) are among the candidates for reparative cells. These cells can potentially be mobilized into the circulation in response to injury signals and exert their reparative effects at the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
147
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(151 citation statements)
references
References 148 publications
2
147
0
1
Order By: Relevance
“…5 New treatment options include tissue engineering for tissue regeneration, which includes harvesting and transplant methods. 6,7 Tissue auto-transplant is a well-established strategy for treatment of damaged or lost tissue after a trauma, oncological resection, congenital deformities or progressing degenerative disease. 8 In this field stem cells (SC) have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…5 New treatment options include tissue engineering for tissue regeneration, which includes harvesting and transplant methods. 6,7 Tissue auto-transplant is a well-established strategy for treatment of damaged or lost tissue after a trauma, oncological resection, congenital deformities or progressing degenerative disease. 8 In this field stem cells (SC) have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…These endogenous progenitor cells can be mobilized to the PB [1,11,12,15,17,22,36,48,52]. Circulating MSCs, and perhaps other adult stem cells, home to sites of skeletal injury [14,23,29,35,45,54], and increasing the number of adult stem cells at sites of injury aids tissue regeneration [4,8,16,40,43,56] either directly or through trophic effects [5,8,17,53].…”
Section: Introductionmentioning
confidence: 99%
“…19 Importantly, the interaction between CXCL12 and CXCR4 is required for the homing of MSC to the sites of bone healing. 28,29 Wynn et al observed that MSC migrate toward a CXCL12 gradient in a dose-dependent manner. 30 With such a multifactorial impact, the expression levels of both CXCL12 and CXCR4 are therefore highly relevant to osteogenesis, and increased levels would be considered a strong advantage of one scaffold over another.…”
mentioning
confidence: 99%